PERBEDAAN PENGARUH LATIHAN DOUBLE LEG TUCK JUMP DAN LATERAL BOUND TERHADAP PENINGKATAN POWER OTOT TUNGKAI DAN HASIL SMASH PADA ATLET PUTRA - Sibuea, Marfin Prada; Wiyaka, Ibrahim (JURNAL ILMU KEOLAHRAGAAN, 2025)
Volleyball is a sport that requires speed, agility, and overall body strength. The power of the leg muscles has a very important role in the game of volleyball because it contributes directly to the various explosive movements that athletes need. Smash is one of the main attack techniques in volleyball that aims to score points by directing the ball hard and sharply into the opponent's area. This study aims to determine the difference in the effect of double leg tuck jump and lateral bound exercises on the increase in leg muscle power and smash results in male volleyball athletes. The research method used was experimental research (treatment) with a data collection technique involving two independent variables and one bound variable. The results of this study are (1) There is an effect of double leg tuck jump training on increasing leg muscle power in Club Toba Jaya VC Toba men's volleyball athletes, (2) There is an effect of lateral bound training on increasing leg muscle power in Club Toba Jaya VC Toba men's volleyball athletes, (3) Double leg tuck jump training is not more influential when compared to lateral bound training on increasing leg muscle power in Club volleyball men's athletes Toba Jaya VC Toba, (4) There is an effect of double leg tuck jump training on smash results in Club Toba Jaya VC Toba men's volleyball athletes, (5) There is an effect of lateral bound training on smash results in Club Toba Jaya VC Toba men's volleyball athletes, (6) Double leg tuck jump training is not more influential than lateral bound training on smash results in Club Toba Jaya VC Toba men's volleyball athletes